2019
DOI: 10.25259/sni-235-2019
|View full text |Cite
|
Sign up to set email alerts
|

Acute paradoxical brain herniation after decompressive craniectomy for severe traumatic brain injury: A case report

Abstract: Background: Sinking skin flap syndrome or paradoxical brain herniation is an uncommon neurosurgical complication, which usually occurs in the chronic phase after decompressive craniectomy. We report a unique case presenting with these complications immediately after decompressive craniectomy for severe traumatic brain injury. Case Description: A 65-year-old man had a right acute subdural hematoma (SDH), contusion of the right temporal lobe, and diffuse traumatic subarachnoid hemorrhage with midline shift to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(23 reference statements)
0
10
1
Order By: Relevance
“…Paradoxical herniation has been reported after craniotomy in the context of CSF hypovolemia, usually ascribed to intraoperative or postoperative CSF drainage or spinal CSF fistula[ 1 , 3 - 5 ]. Currently, only a few cases have been reported that paradoxical herniation may occur in the absence of CSF drainage, which is somewhat different from our case[ 6 - 8 ]. We describe a unique case of spontaneous paradoxical herniation after intravenous infusion of mannitol and decompressive craniectomy.…”
Section: Introductioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Paradoxical herniation has been reported after craniotomy in the context of CSF hypovolemia, usually ascribed to intraoperative or postoperative CSF drainage or spinal CSF fistula[ 1 , 3 - 5 ]. Currently, only a few cases have been reported that paradoxical herniation may occur in the absence of CSF drainage, which is somewhat different from our case[ 6 - 8 ]. We describe a unique case of spontaneous paradoxical herniation after intravenous infusion of mannitol and decompressive craniectomy.…”
Section: Introductioncontrasting
confidence: 92%
“…Paradoxical herniation, a rare complication of patients who have undergone craniotomy, refers to transtentorial herniation in the context of intracranial hypotension[ 3 , 6 ]. This life-threatening complication has been reported after various types of CSF depletion and drainage, including CSF leakage, lumbar puncture, lumbar drain, CSF shunt, and ventriculostomy in patients undergoing a decompressive craniectomy[ 4 , 9 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations